Recurrence of Febrile Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1992)
The predictive value of multiple clinical variables for febrile seizure recurrence was assessed in a follow-up study of 155 Dutch children at the Department of Paediatrics, University Hospital and Sophia Children's Hospital, Rotterdam, The Netherlands.